Australia and Other Nations are Failing to Meet Sedentary Behaviour Guidelines for Children: Implications and a Way Forward - Straker, Leon; Howie, Erin; Cliff, D.; Davern, M.; Engelen, L.; Gomersall, S.; Ziviani, J.; Schranz, N.; Olds, T.; Tomkinson, G. (2015)
BACKGROUND: Australia has joined a growing number of nations which have evaluated the physical activity and sedentary behaviour status of their children. Australia received a 'D minus' in the first Active Healthy Kids Australia Physical Activity Report Card. METHODS: An expert subgroup of the Australian Report Card Research Working Group iteratively reviewed available evidence to answer three questions: 1) What are the main sedentary behaviours of children?, 2) What are the potential mechanisms for sedentary behaviour to impact on child health and development? and, 3) What are the effects of different types of sedentary behaviours on child health and development? RESULTS: Neither sedentary time nor screen time are homogeneous activities likely to result in homogenous effects. There are several mechanisms by which various sedentary behaviours may positively or negatively affect cardiometabolic, neuro-musculoskeletal, and psycho-social health, though the strength of evidence varies. National surveillance systems, and mechanistic, longitudinal and experimental studies are needed for Australia and other nations to improve their grade. CONCLUSIONS: Despite limitations, available evidence is sufficiently convincing that the total exposure and pattern of exposure to sedentary behaviours are critical to the healthy growth, development and wellbeing of children. Nations therefore need strategies to address these common behaviours.